2.15 or Not 2.15? An Historical‐Analytical Inquiry into the Nearest‐Neighbor Statistic. Issue 2 (20th March 2021) - Philo, Chris; Philo, Peter
Abstract : Nearest‐neighbor analysis (NNA)—a method for assessing the degree to which a spatial point pattern departs from randomness in the direction of being either clustered or regular—was imported into academic geography from an article published in 1954 by ecologists Clark and Evans. In its simplest form, concerned with distances to the first nearest neighbor, NNA hinged on the behavior of the "nearest‐neighbour statistic, " Rn, supposed to vary between 0 (complete clustering) and 2.15 (complete regularity). NNA and the wider body of work on point pattern analysis quickly gained in sophistication, meaning that this simple test statistic only featured briefly in the frontline research literature of geographical analysis. Nonetheless, given its easy‐to‐grasp logic, it became and remains a staple of quantitative geography textbooks for undergraduate students and statistical methods training in school‐level geography curricula. The purpose of this paper is to chart the history of NNA and its test statistic in academic geography, and to provide an analytical demonstration that the value of 2.15 has been mistakenly identified as an upper limit for the latter. Broader speculations are then offered about what may be learned from the history of how the discipline has handled this statistic.